SISTEM INFORMASI TARIAN ADAT INDONESIA BERBASIS MULTIMEDIA (Information Technology and Telematics, 2015)
Abstract: Maintenance culture is not only done by bequeathing to the next generation, but also can take advantage of advances in technology to store it into a database that is not influenced by the development of a new culture, so it can be utilized properly and can be disseminated by means of a multimedia-based information systems can be accessed by the public. This study aims to create an information about the diversity of cultures (traditional indigenous dance). Literature methods used for data collection in the making of this system. The database in this system is dynamic (can be updated). This system can be used by the general public as well as by the students as a learning medium This research resulted in Indonesian Traditional Dance Information System Based Multimedia. The system was then tested and can run well. This research can be developed by adding a variety of information about diversity traditional indigenous culture, especially dance. Keywords: Traditional Indonesian Dance Information System Based Multimedia